2014
DOI: 10.1002/2014jd021908
|View full text |Cite
|
Sign up to set email alerts
|

WWBs, ENSO predictability, the spring barrier and extreme events

Abstract: This study examines how semi-stochastic Westerly Wind Bursts (WWBs) affect El Niño Southern Oscillation (ENSO) predictability. An ensemble ENSO prediction experiment is presented in which the Community Climate System Model version 3 (CCSM3) and CCSM3 with a state-dependent WWB parameterization are used as both "truth" and as predictor systems. Inclusion of WWBs has little effect on ENSO predictability if the "truth" lacks WWBs. If the "truth" includes WWBs, the limit of ENSO predictability is larger for a fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 79 publications
5
64
0
Order By: Relevance
“…The interaction between SST and WWBs has previously been shown to be an important contributor to adequate simulation and prediction of ENSO events (Gebbie et al, ). Previous studies show that models that represent state‐dependent noise can represent the extreme El Niño statistic better than the models that do not have a state‐dependent high‐frequency variability in winds (Lopez & Kirtman, , ; Takahashi & Dewitte, ). Our results show that the statistics of the zonal wind changes in response to the aforementioned ENSO feedbacks.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between SST and WWBs has previously been shown to be an important contributor to adequate simulation and prediction of ENSO events (Gebbie et al, ). Previous studies show that models that represent state‐dependent noise can represent the extreme El Niño statistic better than the models that do not have a state‐dependent high‐frequency variability in winds (Lopez & Kirtman, , ; Takahashi & Dewitte, ). Our results show that the statistics of the zonal wind changes in response to the aforementioned ENSO feedbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Menkes et al (2014) showed that the lack of WWBs in boreal spring and summer is responsible for the weak El Niño in 2014. Lopez and Kirtman (2014) proposed that the spring prediction barrier of ENSO is partially caused by the lack of the WWBs in the forecast models. Improving the air-sea coupling may improve WWBs simulation in CCSM4, and may further improve the ENSO predictability in models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…westerly wind burst (WWB)] on the diversity and predictability of El Niño events (Hu et al 2014;Chen et al 2015). Particularly, Lopez and Kirtman (2014) indicated the SPB is due to the presence of WWB because significant WWB activities can contribute to a rapid drop off in signal-to-noise ratio of coupled system in spring. Actually, comparison between these studies associated with atmospheric effects and the present study proposes a new question to the SPB: is the SPB more sensitive to ocean state or variations in atmosphere?…”
Section: Discussionmentioning
confidence: 99%